2018
DOI: 10.1016/j.biopsych.2017.04.011
|View full text |Cite|
|
Sign up to set email alerts
|

β-Amyloid Precursor Protein Intracellular Domain Controls Mitochondrial Function by Modulating Phosphatase and Tensin Homolog–Induced Kinase 1 Transcription in Cells and in Alzheimer Mice Models

Abstract: Overall, we delineate a molecular cascade presenilins-AICD-Forkhead box O3a linking parkin to Pink-1. Our study demonstrates AICD-mediated Pink-1-dependent control of mitochondrial physiology by presenilins. Furthermore, it unravels a parkin-Pink-1 feedback loop controlling mitochondrial physiology that could be disrupted in neurodegenerative conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 75 publications
(88 reference statements)
3
41
0
Order By: Relevance
“…It was also shown that Aβ molecules can form pores permeable for Ca 2+ in the cell membrane and additionally disturb calcium homeostasis, contributing to the formation of free oxygen radicals. Oxidative stress caused by the accumulation of Aβ and calcium excess may contribute to the mitochondrial dysfunction [44]. Early accumulation of structurally abnormal mitochondria was observed in AD patients and a similar change was observed in AD animal models [43,44].…”
Section: Alzheimer's Diseasementioning
confidence: 90%
“…It was also shown that Aβ molecules can form pores permeable for Ca 2+ in the cell membrane and additionally disturb calcium homeostasis, contributing to the formation of free oxygen radicals. Oxidative stress caused by the accumulation of Aβ and calcium excess may contribute to the mitochondrial dysfunction [44]. Early accumulation of structurally abnormal mitochondria was observed in AD patients and a similar change was observed in AD animal models [43,44].…”
Section: Alzheimer's Diseasementioning
confidence: 90%
“…Mutations in PINK1 and PARK2 contribute to obvious mitochondrial dysfunctions, leading to degeneration of muscles and neurons [ 120 ]. Abnormal mitochondrial accumulation in AD is thought to be caused by multiple mechanisms of mitophagy defects, such as the impaired PS1/γ-secretase–amyloid precursor protein intracellular domain–PINK1 transcription axis [ 121 ]. In PD, PARK6 (coding PINK1) and PARK2 (coding Parkin) gene mutations will cause 5% of familial PD [ 122 ].…”
Section: Main Textmentioning
confidence: 99%
“…In the amyloidogenic pathway, C99 is engaged by the heterotetrameric γ‐secretase complex, which binds C99 monomers and initially cuts C99 at either of two possible “epsilon cleavage” sites in the membrane near the cytosol, resulting the in the release of the amyloid intracellular domain (AICD). The function of AICD is controversial, with some evidence suggesting that it plays a role in regulating transcription of certain genes . Intriguingly, some of the these genes encode proteins clearly related to the amyloidogenic pathway or to tau hyperphosphorylation and fibrillization .…”
Section: Components Of the Amyloidogenic Pathwaymentioning
confidence: 99%